Original paperEndothelial cell markers in coronary artery disease - Lampka, Magdalena; Grąbczewska, Zofia; Krajewska, Maria; Hołyńska-Iwan, Iga; Kubica, Jacek; Tyrakowski, Tomasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Background : Endothelial injury, activation and dysfunction play an important role in atherosclerosis progression and development of cardiovascular disease. Aim : To evaluate biochemical markers assessing the vascular endothelium state in patients with coronary artery disease. Material and methods : We examined 57 patients with coronary artery disease (CAD): 27 patients with acute myocardial infarction (AMI) and 30 patients with stable angina pectoris (SA). The control group comprised 23 patients without symptoms of CAD. The concentration of von Willebrand factor (vWF), thrombomodulin (sTM), endothelin-1 (ET-1), and adhesion molecules (soluble intercellular adhesion molecule-1 (sICAM-1) and soluble vascular cell adhesion molecule-1 (sVCAM-1)) was analysed in plasma or serum. Results : A significant increase in vWF, sICAM-1, sVCAM-1 and ET-1 concentrations was found in AMI compared to the control group. Increased vWF and sICAM-1 concentrations were found in SA compared to the control group. The AMI group was characterized by significantly higher vWF concentration than the SA group. Thrombomodulin concentration did not differ significantly between any patient groups and the control group. There was a positive correlation between vWF concentration and sVCAM-1 and sTM concentrations, and an inverse correlation between ET-1 and sICAM-1 concentrations in AMI. A sICAM-1 correlated positively with sVCAM-1 concentration in SA. Conclusions : von Willebrand factor is more useful than sTM, endothelin-1, and cell adhesion molecules sICAM-1 and sVCAM-1 to assess endothelium state in patients with CAD. The increase in plasma vWF concentration confirms endothelial injury and/or activation in CAD and indicates a greater severity of these disorders in AMI than in SA.